National tourism standards and local practices: Based on the experience of Tibet, China. Issue 6 (1st December 2022) - Ji, Zhongjuan; Xu, Honggang; Cui, Qingming; Yang, Peng
ABSTRACT: Tourism standards are critical to standardizing the development of the tourism industry. Tourist attractions, being the core of tourism products, have a variety of characteristics and individualities. It is however, difficult to standardize different types of tourist attractions according to the same tourism standards. Such standardization is also incompatible with tourist attractions' construction according to the national tourism standards from the local perspective. Therefore, it is necessary to identify the universality and particularity of tourism products and their influence on establishing tourism standards. From the perspective of placeness, it is essential to explore how to improve the fairness and universality of national tourism standards. This study takes the Tibet Autonomous Region as a case to reveal the theoretical basis of tourism standards by considering regional development imbalances and diversity of tourism products. The research shows that the core framework and principles should be unified when National Tourism Standards are applied to local practice but attach importance to the weightage of the software facilities scoring and leave space for the finer details. So that tourism standards can be adapted to different regions to develop tourism with local characteristics. This study enriches the theoretical basis study of tourism standards.